Analisis faktor-faktor yang mempengaruhi pergantianKantor akuntan publik(Studi Kasus Pada Perusahaan Perbankan yang Terdaftar di Bursa Efek IndonesiaPeriode 2010-2014) - Basuki, Jarita Inez, Dr. Erma Setiawati, MM, CA (2016)
Auditor switching is a changes of auditor performed by the client company either mandatory or voluntary. This study aims to examine the factors that influence of auditor switching. The variables used in this study is the audit opinion, KAP size, financial distress, percentage change in ROA and management changes. The population of the sample were banking companies listed in Indonesia Stock Exchange 2010-2014. The sample is determined by using purposive sampling. The study had 65 samples from 13 companies. In this study, the hypothesis was tested using logistic regression analysis. The results of this study indicate that the audit opinion influence on auditor switching. While the KAP size, financial distress, percentage change in ROA, and change management has no effect on the change of KAP.